Targeting endothelin-1 receptor/β-arrestin1 network for the treatment of ovarian cancer. (3rd October 2017) - Rosanò, Laura; Cianfrocca, Roberta; Sestito, Rosanna; Tocci, Piera; Di Castro, Valeriana; Bagnato, Anna
ABSTRACT: Introduction : Endothelin-1 receptor (ET-1R)/β-arrestin1 (β-arr1) signaling is dysregulated in ovarian cancer. This signaling circuit enables cancer cells to engage several signaling and transcriptional networks that are pervasively intertwined, and represent a potential therapeutic target for developing novel agents for ovarian cancer treatment. Areas covered : In this article, we discuss the role of the signaling network between ET-1R and key pathways mediated by the scaffold protein β-arr1, as part of signaling complex, or as a transcription co-activator, promoting precise control of transcription of different genes, including ET-1. Therefore ET-1R/β-arr1 is an actionable node involved in the activation of a persistent feedback loop that contributes to bypass signaling. Targeting ET-1R empowering this circuit can represent a necessary measure to reach clinical efficacy. Preclinical studies demonstrate that blocking ET-1R by FDA approved dual ETA R/ETB R antagonist prevents β-arr1 network formation, offering a novel therapeutic strategy in ovarian cancer patients. Expert opinion : The information provided in this review about the ET-1R/β-arr1 hub represents an invaluable tool for both identifying the interconnected pathways involved in ovarian cancer and targeting them more effectively. The new perspective arising from ET-1R therapeutics will likely prompt a valuable frame for the design of new promising combinatorial therapy, blocking compensatory networks.